Looking back and going forward: The concept of the public in public relations theory. (September 2019) - Pieczka, Magda
This article examines the development of the public as a foundational concept in public relations theory. It provides an overview of the way in which public relations has understood the term as referring to two distinct phenomena of a public and the public. The article approaches public relations theory as unfolding of a narrative identity of public relations. The discussion subsequently reaches to the work of Michael Warner and Judith Butler to consider the limitations and implications of the situational theory of publics and the deliberativist approach to the public derived from the work of John Dewey and Jürgen Habermas. In its final sections, the article redefines the public as a family of three distinct, but at times, overlapping terms: an audience as a public of shared spaces, a self-organized public of shared attention, and the public as a political and social imaginary. This article argues for the need to adopt the performative approach to the public in order to tackle some of the biases in public relations theory. It also suggest the PESO model of communication a useful starting point to create a more complex understanding of the formation of the public (in all three senses) in relation to processes of co-creation and circulation of a wide range of texts.